Rhegmatogenous retinal detachment presentation and surgery in uveitic eyes. Issue 1 (29th July 2021) - Young-Zvandasara, Tafadzwa; Brunner, David; Welch, Sarah; Sims, Joanne L; De Souza, Clairton; Cunningham, William J; Niederer, Rachael L
Abstract : Background/aims: To explore the occurrence, uveitis activity, features, rate of proliferative vitreoretinopathy (PVR) and outcomes following rhegmatogenous retinal detachment (RRD) in a large tertiary referral uveitis service. Methods: Retrospective analysis of subjects attending between 2008 and 2019. Multivariate analysis of risk factors for RRD was calculated. Nelson-Aalen plots were used to demonstrate cumulative risk of RRD. Outcomes of RRD surgery and prognostic indicators were analysed. Results: Two thousand four hundred and forty-seven (2447) subjects (3516 eyes) with uveitis included. The mean follow-up was 5.7 years (19 767 eye-years); 56 eyes developed a RRD (1.6%). Thirty-two eyes had surgery in our unit. Risk factors for RRD were posterior uveitis or panuveitis (HR 3.386, p<0.001), male gender (HR 2.045, p=0.029) and infectious aetiology (HR 1.942, p=0.044). PVR was present in six (18.8%) eyes at presentation, and a further four (12.5%) developed it after the primary surgery. Final follow-up data showed 16 (50%) moderate or severe visual loss, although 29 (90.6%) had anatomical reattachment without oil in situ. Conclusions: There is a high rate of RRD in uveitis eyes. This is accompanied by high rates of PVR and redetachment. Anatomical success was high, but visual outcomes remain unpredictable.